Evaluasi atas Pelaksanaan Undang-Undang Nomor 24 Tahun 2000 tentang Perjanjian Internasional - Haryono, Harry P. (Indonesian Journal of International Law, 2007)
The Law Number 24 Years 2000 on International Agreement has been implemented for more than 5 years, thus the evaluation of its implementation needs to be done, whether it has accomplished its own purpose when it was made or not. The main point is the question does it have to be changed ? this article gives guidance through some questions to answer the main question. Some advices, such as how important is to make people who have the authority to construct international agreement understand what they have to do, and the background of the formulation of that Law, have been given as well.